Does the Position in Business Group Hierarchies Affect Workers' Wages? - Elke Jahn; Hartmut Egger; Stefan Kornitzky (ZBW - Leibniz Information Centre for Economics, 2021)
We merge firm-level data on ownership linkages with administrative data on German workers to analyze how the position in a business group hierarchy affects workers' wages. To acknowledge that ownership linkages are not onedirectional, we propose an index to measure hierarchical distance to the ultimate owner. After controlling for unobserved heterogeneity and selection into the business group hierarchy, we find a positive effect of larger hierarchical distance to the ultimate owner of a business group on workers' wages. This result is in line with a monitoring-based theory of business group hierarchies, in which larger hierarchical distance to the ultimate owner is associated with lower monitoring efficiency and thus higher wage payments to incentivize workers
Keywords: C23; J31; L23; 330; Business groups; ownership networks; workers wages; differencein-difference; hierarchical distance